Peran Tenaga Pendidik dalam Meningkatkan Mutu Pendidikan di Diniyah Takmiliyah Awaliayah Nurul Huda Napal Sisik Muara Bulian - Diki Nurdwiyanto; Khairul Mutaqin; Yulia Putri (Universitas Palangka Raya, 2025)
Educators play a role in improving the quality of education. It includes a series of processes designed to ensure National Education Standards (SNP) are achieved, including program evaluation, student assessment, and effective curriculum development. With quality, educational institutions can ensure students get a quality learning experience, according to their needs. The role of educators is also to help identify areas that need improvement, enabling corrective steps to increase learning effectiveness.